Folic acid modifies the shape of epithelial cells during morphogenesis via a Folr1 and MLCK dependent mechanism - Jessica B. Martin; Maria Muccioli; Kenneth Herman; Richard H. Finnell; Timothy F. Plageman (Biology Open, 2019)
Folic acid supplementation can prevent neural tube defects, but the specific molecular mechanisms by which it does have not been elucidated. During neural plate morphogenesis, epithelial cell apical constriction cooperates with other events to drive tissue-bending, and when defective, can result in neural tube defects. A Rho-kinase deficient binding mutant of the apical constriction regulating protein, Shroom3 (Shroom3R1838C), is one of only a handful of mouse mutant lines with neural tube defects that can be rescued by folic acid supplementation. This provided a unique opportunity to probe the functional rescue of a protein linked to neural tube development by folic acid. Utilizing an epithelial cell culture model of apical constriction, it was observed that treatment with exogenous folic acid, as well as co-expression of the folic acid receptor Folr1, can rescue the function of the Rho-kinase binding deficient mutant of Shroom3 in vitro. It was also determined that the rescuing ability of folic acid is RhoA and Rho-kinase independent but myosin light chain kinase (MLCK) and Src-kinase dependent. Inhibition of Rho-kinase-dependent apical constriction in chick embryo neural epithelium was also observed to be rescued by exogenous folic acid and that treatment with folic acid is accompanied by elevated activated myosin light chain and MLCK. Furthermore, doubly heterozygous mouse embryos lacking one copy each of Shroom3 and Folr1 exhibit a low rate of neural tube defects and also have lower levels of activated myosin light chain and MLCK. These studies suggest a novel mechanism by which folic acid modifies epithelial cell shape during morphogenesis, shedding light onto how folic acid may prevent neural tube defects.